1996
DOI: 10.1159/000189341
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Nitrogen Low-Phosphorus Vegan Diet for Patients with Chronic Renal Failure

Abstract: The nutritional treatment of chronic renal failure with a low-protein low-phosphorus diet (conventional low-protein diet, CLPD) is effective in reducing uremic intoxication, slowing the progression of renal failure and preventing secondary hyperparathyroidism. Unfortunately, in some patients, the poor palatability and the high cost of the protein-free substitutes, together with difficulties in following the diet away from home, can make good compliance difficult, possibly causing low energy intake and malnutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 10 publications
3
75
0
1
Order By: Relevance
“…An encouraging finding is that fruits and vegetables did not induce hyperkalemia in nondiabetic individuals with mean creatinine clearance of 16.1 ml/min per 1.73 m 2 (13). In our study, plasma [K + ] did not change significantly in the fruits and vegetables group, and no patient in any group had plasma [K + ] levels .…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…An encouraging finding is that fruits and vegetables did not induce hyperkalemia in nondiabetic individuals with mean creatinine clearance of 16.1 ml/min per 1.73 m 2 (13). In our study, plasma [K + ] did not change significantly in the fruits and vegetables group, and no patient in any group had plasma [K + ] levels .…”
Section: Discussionsupporting
confidence: 56%
“…Such diets can induce metabolic acidosis in individuals with reduced GFR, including otherwise healthy elderly persons (28). Changing from standard industrialized society diets to a low-phosphorous vegan diet improved metabolic acidosis in patients with CKD who had a mean GFR of 16.1 ml/min (13). In addition, added fruits and vegetables reduced urine NAE, consistent with reduced net endogenous acid production (28), in individuals with CKD stage 2 (eGFR, 60-89 ml/min per 1.73 m 2 ) but without metabolic acidosis (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VLPD (0.3-0.4 g/kg body weight/d protein) is a vegetarian diet that mainly includes vegetables and fruits and is supplemented with essential aminoacids and ketoacids (69). To maintain a neutral nitrogen balance, though the protein intake is below the minimum required threshold, ketoacids are given to allow endogenous nitrogen recycling as a means of building the essential aminoacids from the relative ketoacids, thus further contributing to reduce serum urea levels (70).…”
Section: Would a Vlpd/ketodiet Be Indicated For This Patient?mentioning
confidence: 99%
“…It has been shown that a low-protein, lowphosphorus diet protects remnant glomeruli from further sclerotic changes and delays end stage renal disease (ESRD) (Zandik et al, 1998). Thus, an appropriate diet is critically important in the management of patients with CRF, because it offers several advantages and benefits (Giovannetti and Maggmore, 1964;Giovannetti, 1985;Barsotti et al, 1996).…”
Section: Introductionmentioning
confidence: 99%